Head-centric computing for vestibular stimulation under head-free conditions - La Scaleia, Barbara; Brunetti, Claudia; Lacquaniti, Francesco; Zago, Myrka (Frontiers in Bioengineering and Biotechnology, 2023)
The vestibular end organs (semicircular canals, saccule and utricle) monitor head orientation and motion. Vestibular stimulation by means of controlled translations, rotations or tilts of the head represents a routine manoeuvre to test the vestibular apparatus in a laboratory or clinical setting. In diagnostics, it is used to assess oculomotor or perceptual responses, whose abnormalities can reveal subclinical vestibular dysfunctions due to pathology, aging or drugs. Objective: The assessment of the vestibular function requires the alignment of the motion stimuli as close as possible with reference axes of the head, for instance the cardinal axes naso-occipital, interaural, cranio-caudal. This is often achieved by using a head restraint, such as a helmet or strap holding the head tightly in a predefined posture that guarantees the alignment described above. However, such restraints may be quite uncomfortable, especially for elderly or claustrophobic patients. Moreover, it might be desirable to test the vestibular function under the more natural conditions in which the head is free to move, as when subjects are tracking a visual target or they are standing erect on the moving platform. Here, we document algorithms that allow delivering motion stimuli aligned with head-fixed axes under headfree conditions. Methods: We implemented and validated these algorithms using a MOOG-6DOF motion platform in two different conditions. 1) The participant kept the head in a resting, fully unrestrained posture, while inter-aural, naso-occipital or cranio-caudal translations were applied. 2) The participant moved the head continuously while a naso-occipital translation was applied. Head and platform motion were monitored in real-time using Vicon. Results: The results for both conditions showed excellent agreement between the theoretical spatio-temporal profile of the motion stimuli and the corresponding profile of actual motion as measured in real-time. Conclusion: We propose our approach as a safe, non-intrusive method to test the vestibular system under the natural head-free conditions required by the experiential perspective of the patients.